DIRECT MEDICAL COST AND LENGTH OF STAY OF HYPERTENSION PATIENTS AT PRIVATE HOSPITAL IN YOGYAKARTA - Faridah Baroroh; Ridhaul Maghfiroh (Universitas Muhammadiyah Magelang, 2023)
The province that ranks fourth with the highest incidence of hypertension in Indonesia is the Special Region of Yogyakarta (DIY). Hypertension therapy is carried out in a not short period, so it becomes an economic burden for people with hypertension and the government. This study aims to determine the relationship between the length of hospitalization and direct medical costs—an analytical observational research method with retrospective data collection and data from class III inpatient hypertensive medical records. The calculation of costs is viewed from a payer's perspective—descriptive and analytical data analysis to determine the relationship between the length of hospitalization and direct medical costs. The study's results of 41 patients met the criteria; 53.65% were women aged 22-59 years (53.65%). The most widely used antihypertensive drug was the combination of amlodipine + candesartan (26.82%). The average direct medical costs for hypertensive patients were IDR 7,039,515. The highest direct medical cost component is the cost of other drugs and medical equipment. The component of direct medical costs is the lowest cost of antihypertensive drugs. The average length of hospitalization for hypertensive patients is 6.14 days. There was a significant relationship (p=0.000) between the length of hospitalization and direct medical costs. The conclusion of this study is a significant relationship (p = 0.000) between the length of hospitalization and direct medical costs